2013
DOI: 10.1136/bcr-2012-008538
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on mental capacity assessments in general hospitals

Abstract: Research suggests that a significant proportion of inpatients in general medical wards may lack capacity to make treatment decisions, a situation that often goes unrecognised by clinicians. We would like to briefly discuss two cases from a non-psychiatric setting, where a mental disorder served to inhibit the individual's ability to weigh-up associated risks when deciding to refuse potentially life-sustaining healthcare interventions. In both cases the history of mental disorder was well established yet, for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…This means that physicians identified as incompetent, less and different patients than those rated as such by the investigators. It seems that our results largely confirm that of previous research [ 6 , 18 , 23 ], which showed that only a small proportion (25-42%) of incapable patients in medical wards are recognized by their physician as such. The replication of this finding suggests that a proportion of patients in medical wards of general hospitals are undergoing treatment while they lack capacity to provide valid informed consent.…”
Section: Discussionsupporting
confidence: 91%
“…This means that physicians identified as incompetent, less and different patients than those rated as such by the investigators. It seems that our results largely confirm that of previous research [ 6 , 18 , 23 ], which showed that only a small proportion (25-42%) of incapable patients in medical wards are recognized by their physician as such. The replication of this finding suggests that a proportion of patients in medical wards of general hospitals are undergoing treatment while they lack capacity to provide valid informed consent.…”
Section: Discussionsupporting
confidence: 91%
“…Most previous studies have focused on assessments for two different groups: people with learning disabilities and those with mental health conditions [e.g., 32,33]. In the current study, most participants indicated that they did not carry out assessments for these groups of patients very often.…”
Section: Discussionmentioning
confidence: 74%
“…For example, SLTs might be involved in assessments for people with communication difficulties [36,40]. Two studies [36,38] described the involvement of mental health specialists (e.g., liaison psychiatrists or mental health nurses) in capacity assessments for patients with mental health conditions. The authors of two case studies [38] suggested that multidisciplinary assessments of these patients' decision-making abilities were more accurate when they involved psychiatrists with specialist knowledge of mental health presentations.…”
Section: Choice Of Assessormentioning
confidence: 99%
“…Two studies [36,38] described the involvement of mental health specialists (e.g., liaison psychiatrists or mental health nurses) in capacity assessments for patients with mental health conditions. The authors of two case studies [38] suggested that multidisciplinary assessments of these patients' decision-making abilities were more accurate when they involved psychiatrists with specialist knowledge of mental health presentations. Participants in two studies [33,36] suggested that the choice of assessor could depend on which discipline understood the nature of the decision a patient was being asked to make and the decision options available to her/him.…”
Section: Choice Of Assessormentioning
confidence: 99%
See 1 more Smart Citation